Behavioral Analysis of Maternal Filicide - Shelton, Joy Lynn E.; Hoffer, Tia A.; Muirhead, Yvonne E. (SpringerBriefs in Psychology, 2015)
They are shocking acts of violence that confuse and disturb the general public. And because of their relative rarity, cases of mothers killing their children also puzzle professionals in law enforcement and psychology on issues of causation and punishment, treatment and rehabilitation. Bringing mental health and criminal justice perspectives together, Behavioral Analysis of Maternal Filicide examines these complex crimes in the context of what is known about women and violence, and of society's expectations of women. This concise reference reviews psychological, behavioral, and societal dynamics of motherhood, correcting the simplistic "mad mother"/"bad mother" constructs that lead to inconsistent treatment in judicial settings. Findings based on psychiatric and forensic studies identify social and family risk factors for maternal filicide as well as factors that may change as children develop. Additionally, the discussion section offers implications for professionals in legal and mental health disciplines for putting this knowledge to practical use. Featured in this volume: Theories of general violence and female violence. The mother/child dynamic: attachment styles and child development. The "insanity" of reproduction: literature review on postpartum disorders. Personality disorders and their relationship to violence. Results of a detailed FBI study of maternal filicide cases, with legal outcomes. Considerations for the criminal justice system and the mental health community. Illuminating a hidden area of domestic abuse, Behavioral Analysis of Maternal Filicide is an essential resource for law enforcement and mental health professionals dealing with female violence, the mother-child dynamic, and mental disorders, and particularly those addressing, investigating, and prosecuting maternal filicide offenders.  .